Radical total gastrectomy for gastric cancer complicated by hepatic sinusoidal obstruction syndrome: a case report - Gao, Bin; Zhang, Jingjing; Zhu, Lei; Zhang, Yaming (Frontiers in Medicine, 2025)
Hepatic sinusoidal obstruction syndrome (HSOS) is often caused by the ingestion of pyrrolizidine alkaloids (PAs). To date, research on PAs-induced HSOS remains limited. Due to differing etiologies of HSOS in Western and Eastern populations, the clinical features, imaging findings, treatment approaches, and outcomes of HSOS caused by hematopoietic stem cell transplantation or oxaliplatin may not be directly applicable to PAs-induced HSOS. PAs-induced HSOS commonly presents with painful hepatomegaly, ascites, and jaundice. Laboratory tests commonly show abnormal liver function in patients with PA-induced HSOS. Contrast-enhanced computed tomography and magnetic resonance imaging often reveal distinctive imaging features and significant histopathological liver changes in PAs-induced HSOS. These findings highlight the effectiveness of radiological imaging and liver biopsy as diagnostic tools. Treatment strategies for PAs-induced HSOS include fluid management, anticoagulation therapy, glucocorticoids, transjugular intrahepatic portosystemic shunt (TIPS), and liver transplantation. However, managing PAs-induced HSOS remains challenging. This paper presents the case of an elderly male diagnosed with gastric cancer complicated by hepatic sinusoidal obstruction syndrome. The diagnosis was based on characteristic imaging findings, a history of pyrrolizidine alkaloids ingestion, and standard diagnostic criteria, including liver biopsy and histological examination. The patient recovered fully after timely diagnosis and treatment, which included radical total gastrectomy, hepatoprotective diuretics, albumin supplementation, and low-molecular-weight heparin therapy.